(untitled) (Fiep Bulletin - online, 2014)
This paper emerged from a research that proposed to analyze the origin and the effects produced by speeches and curriculum practices, about body and feminine sexuality, on the female teacher´s formation that entered the graduation course of Superior School of Physical Education in Pelotas’ Federal University (ESEF/UFPel), in the 1970’s. To reach our objective, initially, we collected the maximum of the existing written registers that treat of the graduation course curriculum. The method used to analyze the documents was the French speech analysis, which has Michel Foucault as one to its most important theoretical. Concerning that the curriculum’s production is markedly male, because it reflects the dominant epistemology, we believe that it materializes and produces gender’s relation. The gender’s stereotypes are many times read over again in the formation process on educational institutions. In this context some question befalls: was about the female pupils’ sexuality that the class gender’s separation deals? Was the sexuality cared when, as we could see in the beginners manual of ESEF, the alumnus were obliged to use uniforms? The physical-sanitary rhetoric trough the Physical Education history has constituted a feminine health ideology? How can we understand, for example, the biological differences among man and woman if we are used to see our body and sexuality minimized to human anatomy only? In this continuous process of sex’s and gender’s identities production, the scholar space by it daily practices, gests, talks or even the silences, helped in maintaining the gender’s differences.